Novel phage lysin Abp013 against Acinetobacter baumannii - Chu, Joash Jun Keat (2022)
As antimicrobial resistance (AMR) continues to pose an ever-growing global health threat, propelling us into a post-antibiotic era, novel alternative therapeutic agents are urgently required. Lysins are bacteriophage-encoded peptidoglycan hydrolases that display great potential as a novel class of antimicrobials for therapeutics. While lysins against Gram-positive bacteria are highly effective when applied exogenously, it is challenging for lysins to access and cleave the peptidoglycan of Gram-negative bacteria due to their outer membrane. In this study, we identify a novel phage lysin Abp013 against Acinetobacter baumannii. Abp013 exhibited significant lytic activity against multidrug-resistant strains of A. baumannii. Notably, we found that Abp013 was able to tolerate the presence of human serum by up to 10%. Using confocal microscopy and LIVE/DEAD staining, we show that Abp013 can access and kill the bacterial cells residing in the biofilm. These results highlight the intrinsic bacteriolytic property of Abp013, suggesting the promising use of Abp013 as a novel therapeutic agent.